Research on Sustainable Development Ability and Spatial-Temporal Differentiation of Urban Human Settlements in China and Japan Based on SDGs, Taking Dalian and Kobe as Examples - Xueping Cong; Xueming Li; Songbo Li; Yilu Gong (Complexity)
The sustainable development of the human settlements (HS) has become a global universal program. The comparison of cities in different countries is of great significance to provide international experience for future urban construction. Combined with the UN 2030 Sustainable Development Goals (SDGs), this paper establishes an evaluation index system for the sustainable development ability of urban HS and constructs a three-dimensional research framework of “development-coordination-sustainability,” which compares the sustainable development ability of the HS of Dalian, China, and Kobe, Japan, from 2005 to 2018 and explores the spatial evolution characteristics and obstacle factors of the HS of the two cities. The results show that (1) the development degree of the HS of the two cities is on the rise. The development level of Kobe is always higher than that of Dalian, and the gap is gradually narrowing; Kobe has advantages in natural and residential environment, while Dalian has advantages in cultural and economic environment. (2) The coordination degree of the development of the HS of the two cities has improved steadily, and the coordination degree of Kobe is better than that of Dalian. (3) The sustainability of the development of the HS of the two cities is fluctuating, and the average sustainable growth rate of Dalian is higher than that of Kobe. (4) The sustainable development space of the HS in Dalian presents a pattern of “high in the south and low in the north,” and the spatial characteristics of the subsystems are different; the main obstacles have changed from economic-natural to economic-natural-cultural-public services, and the obstacles to development in districts are different. (5) The sustainable development space of the HS in Kobe has a high level of development in the southeast, radiating to the surrounding area, and the spatial characteristics of the subsystems are different; the main obstacles have changed from economic-cultural-natural to economic-natural-population, and the obstacles to development in districts are different. Finally, it puts forward targeted suggestions for the sustainable construction of Dalian. This paper can provide methodological reference for quantitative assessment of the sustainable development of HS and provide policy reference for scientific planning of the construction of HS.